A new combination in Exodeconus, Solanaceae / B. Axelius; W. G. D' Arcy - D' Arcy, William G.; Axelius, Barbro (2007)
Cacabus flavus is transferred to the genus Exodeconus
Keywords: Exodeconus; Solanaceae